INTERNATIONAL STUDENTS’ COGNITIVE LOAD IN LEARNING THROUGH A FOREIGN LANGUAGE OF INSTRUCTION: A CASE OF LEARNING USING BAHASA - INDONESIA - Okuni, Ivan Moses; Widyanti, Ari (PEOPLE: International Journal of Social Sciences, 2019)
Previous studies on cognitive load model have been entirely theoretical and there are no empirical studies currently that have been carried out to test the hypotheses in these theoretical models. Therefore, this study is aimed at proving Choi’s cognitive load model using empirical data. The empirical data was collected in a foreign language-learning environment. The research questionnaire was extracted from the work design questionnaire, learning process questionnaire, mental effort, intrinsic load, extraneous load and germane load scales and was administered to foreign students in Indonesia (N=191). Descriptive statistics showed the foreign students’ Indonesian language proficiency (mean = 4.76 and standard deviation = 2.594) and English proficiency (mean =7.72 and standard deviation =1.732). Foreign students have good fluency in English language as compared to Bahasa Indonesia. Structural Equation Modeling (SEM) using SmartPLS was carried out and the researcher found out that there is a significant relationship between physical environment and learner characteristics, physical environment and lecture characteristics, lecture characteristics and learner characteristics and finally lecture characteristics and cognitive load. The researcher also carried out bivariate correlation analysis using SPSS to determine the relationships between cognitive load factors, physical environment, lecture characteristics, and learner characteristics. The researcher found out that learning in Bahasa Indonesia demotivates students, whilst learning in English (which the foreign students are fluent in) encourages investment of germane load, which is good for learning. Also, the ergonomic condition of the classroom influences the extent at which students invest in mental effort and germane load in learning. In conclusion, our results support the cognitive load theory and we recommend more empirical studies be carried out to enhance our understanding of the cognitive load theory.